2011
DOI: 10.1029/2010jg001486
|View full text |Cite
|
Sign up to set email alerts
|

A global comparison between station air temperatures and MODIS land surface temperatures reveals the cooling role of forests

Abstract: [1] Most global temperature analyses are based on station air temperatures. This study presents a global analysis of the relationship between remotely sensed annual maximum LST (LST max ) from the Aqua/Moderate Resolution Imaging Spectroradiometer (MODIS) sensor and the corresponding site-based maximum air temperature (T amax ) for every World Meteorological Organization station on Earth. The relationship is analyzed for different land cover types. We observed a strong positive correlation between LST max and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
199
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(232 citation statements)
references
References 72 publications
15
199
1
1
Order By: Relevance
“…The pixel-specific monthly differences between normalized LST and WB result in a forest stress index (FSI) computed at monthly intervals over the growing season. In spring during low water stress conditions, forests dissipate incoming shortwave solar radiation efficiently through partitioning to the latent heat flux (LE) associated with transpiration, and thereby maintain canopy temperatures close to that of the surrounding air temperatures (Mildrexler, Zhao, & Running, 2011a;Nemani & Running, 1997). The FSI value associated with a water surplus and low thermal stress is low.…”
Section: The Fvi and Its Conceptual Foundationmentioning
confidence: 99%
See 2 more Smart Citations
“…The pixel-specific monthly differences between normalized LST and WB result in a forest stress index (FSI) computed at monthly intervals over the growing season. In spring during low water stress conditions, forests dissipate incoming shortwave solar radiation efficiently through partitioning to the latent heat flux (LE) associated with transpiration, and thereby maintain canopy temperatures close to that of the surrounding air temperatures (Mildrexler, Zhao, & Running, 2011a;Nemani & Running, 1997). The FSI value associated with a water surplus and low thermal stress is low.…”
Section: The Fvi and Its Conceptual Foundationmentioning
confidence: 99%
“…LST from the Moderate Resolution Imaging Spectroradiometer (MODIS) measures the canopy foliage temperature in vegetated areas, a unique and useful ecological parameter because critical temperature dependent physiological processes and associated energy fluxes occur in the vegetated canopy. A global analysis of the relationship between remotely sensed annual maximum LST from the Aqua MODIS sensor and the corresponding site-based maximum air temperature for every World Meteorological Organization station on Earth showed that LST is more tightly coupled to the radiative and thermodynamic characteristics of the Earth's surface (Mildrexler, Zhao, & Running, 2011a). LST is more sensitive to changes in vegetation density compared to T air and captures additional information on the biophysical controls on surface temperature, such as surface roughness and transpirational cooling (Mildrexler et al, 2011a).…”
Section: Land Surface Temperature and The Biophysical Link To Plant Cmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) is the EOM-derived respiration (R EOM ). While the study reported that the annual maximum LST (LST max ) from the Aqua/MODIS sensor increases faster than the site-observed maximum air temperature (T max ) as temperature increases (Mildrexler et al, 2011), the LST from the Terra/MODIS sensor was reported to correlate closely with the air temperature during daytime, nighttime and mean of the both (e.g., Sims et al, 2008;Ueyama et al, 2010). In our studied sites, the average of daytime LST and nighttime LST from the Terra/MODIS sensor also had a close relationship with the corresponding air temperature, with r 2 as high as to 0.91 and regression line approximating 1:1 line (Fig.…”
Section: Description Of the Rersmmentioning
confidence: 99%
“…Water availability, surface type, soil humidity, local atmospheric and surface conditions affect the energy partitioning into latent (LE), sensible (H) and ground heat (G) fluxes (Mildrexler et al, 2011). Surface roughness affects the transferred sensible and latent heat by regulating vertical mixing of air in the surface layer (van Leeuwen et al, 2011), thereby regulating land surface temperature (LST).…”
Section: Introductionmentioning
confidence: 99%